The Effectiveness of Group Counseling in Preventing Addiction to Watching Online Live-Streaming Video Games at 14th State Senior High School in Padang - Aminah Daulay; Netrawati Netrawati (Consilium, 2023)
The addiction to watching live-streamed online video games has become a significant problem, causing many students to experience negative effects from being addicted to watching live-streamed video games almost every day and at all times. The addiction to watching live-streamed video games needs to be prevented as it can disrupt daily functioning. By providing group guidance services, it is hoped that the addiction to watching live-streamed video games can be prevented. This study aims to determine the effectiveness of group guidance in preventing addiction to watching live-streamed online video games among students. This research is a quantitative study of the experimental type, using a one-group pretest and posttest design. The sample for this study consisted of 290 students selected using purposive sampling technique. The research instrument used a questionnaire on addiction to watching live-streamed online video games with a Likert scale model. Data analysis technique used the Wilcoxon Signed Rank Test through SPSS version 20.00. The results of the study show that (1) the addiction to watching live-streamed online video games among students before receiving group guidance services is categorized as low, (2) the addiction to watching live-streamed online video games among students after receiving group guidance services is categorized as very low, (3) there is a significant decrease in the level of addiction to watching live-streamed online video games after the intervention of group guidance. These results indicate the effectiveness of group guidance as a potentially effective strategy in preventing addiction to watching live-streamed online video games among students, with a coefficient of -3.302 and a significant level of 0.001.